The effectiveness of Resource-Based Learning Model in English for Islamic Studies Course in Enhancing Critical Thinking Skill - Heru Saputra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
AbstractThe pace of change in the world is accelerating rapidly. Hence, a powerful way to empower learners is to improve their critical thinking, an essential skill for success. This quantitative paper aimed to measure the effectiveness of a Research-Based Learning (RBL) model in English for Islamic Studies course to improve students' creative thinking skills at Ma'had Al-Jamiah Putra UIN Salatiga. The subjects were 27 students of Ma'had Al-Jamiah chosen by purposive random sampling to determine the experimental class. The data were obtained by using a questionnaire and test containing the indicators of critical thinking. They were analyzed using one group pretest-posttest to measure the effectiveness of the developed model. Based on the result, it was concluded that the RBL model in English for Islamic Studies course effectively improves the critical thinking skill of Ma'had Al-Jamiah students.